PERUVIAN INCOME TAX AND RESTRICTIONS TO DEDUCT CAUSAL EXPENSES - Vásquez Tarazona, Catya (2017)
In the current Consolidated Text of the Law on Income Tax approved by S.D. No. 179-2004-EF and amendments, restrictions have been placed in deduction of costs or expenses that affect the determination of net income, ignoring economic reality. The fact is that in the Law on Income Tax restrictions exist on the deduction of certain expenses conditioning them to advance payment. This generates a higher current expense on income tax in business, what could transgress the principle of contributory capacity. Therefore, we present in this article, the costs analysis subject to restriction described in subsections l) and v) from the Article 37 ° of the mentioned legal basis, which are conditioned to the advanced payment so that they can be deductible in the fiscal year. By applying different collection instruments and data collection techniques of documentary information, it was noted that the Law on Income Tax does not allow proper allocation of the third category costs, since it inadequately restricts the allocation of some expenses.